The Effect of Patterns of Space Circulation on the Understanding and Satisfaction of Visitors to the Museum of Makassar - Nahridzah Mahjubuh Shiber; Muhammad Haristo Rahman; Jusbaeni Jusbaeni (Journal of Civil Engineering, 2025)
The Museum of Makassar, in its capacity as a representative space of urban historyand culture, plays a pivotal role is fostering collective public awareness of city’sheritage. However, the undirected circulation structure of the exhibition spaceengenders a fragmented and unsystematic visitor experience. The objective of thisresearch is to examine visitor circulation patterns in Museum of Makassar andformulate a spatial movement model that is able to integrate curatorial narrativesmore effectively. This research utilizes a qualitative approach, employing directobservation, spatial mapping and spatial configuration analysis to evaluate therelationship between the movement of visitors and their comprehension ofexhibition content. The findings of this research are anticipated to contribute ofthe development of spatial planning strategies for museums that are morecommunicative, directed and inclusive, thereby supporting museum in their roleas inclusive and immersive public learning spaces.